Pulmonary sarcomatoid carcinoma coexisting with tuberculosis: a case report and literature review - Huang, Zhi-Hao; Zhu, Yu-Fei; Zeng, Yun-Yun; Huang, Hui-Yi; Liu, Jia-Qi; Cen, Wen-Chang; Su, Shan (Frontiers in Oncology, 2025)
Pulmonary sarcomatoid carcinoma (PSC) is a rare non-small-cell lung cancer with sarcomatous components or sarcomatoid differentiation, high degree of malignancy, and insensitivity to chemotherapy or radiotherapy. The management of PSC coexisting with tuberculosis (TB) poses a greater challenge, as it necessitates concurrent administration of both anti-TB and anti-neoplastic therapies. The efficacy of anti-PD-1 immunotherapy in non-small-cell lung cancer is promising, but its safety in patients with co-existent TB remains uncertain. Here, we describe a case of advanced PSC coexisting with TB, which experienced progression-free survival (PFS) of over 36 months after receiving anti-TB and anti-neoplastic therapy composed of chemotherapy, vascular targeting therapy, and PD-1 inhibitors simultaneously. The patient is still being followed up with a satisfactory quality of life. This paper is focused on the characteristics and treatment of PSC and discuss the clinical strategies of lung cancer coexisting with TB.